KINERJA PRODUKSI DAN NILAI TAMBAH AGROINDUSTRI EMPING MELINJO DI KOTA BANDAR LAMPUNG - I Rani Mellya Sari; Wan Abbas Zakaria; Muhammad Irfan Affandi (Lampung University, 2015)
The purpose of this research are to analyze the production performance of emping melinjo agroindustry in Bandar Lampung City, and to the added value of emping melinjo agroindustry in Bandar Lampung City. This research was conducted in January until September 2014. Primary and secondary data were collected in this research. The research samples consisted of sixteen people were chosen by stratified random design. There were eight people of sample from each village. The methods of data analysis used in this research was descriptive, qualitative and quantitative analysis. Analysis production performance and analysis of employment used to answer the first purpose, whereas analysis of added value was used to answer the second purpose. The result of this research showed that performance of emping melinjo agroindustry in Bandar Lampung city in overall was benefit. Productivity of agroindustry in Rajabasa Village was already good with a capacity of 86 percent. Productivity of agroindustry in Sukamaju Village was already good also with a capacity of 84 percent. Agroindustry of emping melinjo in Bandar Lampung city provide added value. Rajabasa village provided an added value of 45.95 percent, whereas Sukamaju village provided an added value of 48.63 percent. Key words: emping melinjo, production performance and value added